Fat pig a play - LaBute, Neil 1963- (Faber and Faber, 2005)
Cow. Slob. Pig. How many insults can you hear before you have to stand up and defend the woman you love? Tom faces just that question when he falls for Helen, a bright, funny, sexy young woman who happens to be plus-sized -- and then some. Forced to explain his new relationship to his shallow (although shockingly funny) friends, he finally comes to terms with his own preconceptions of the importance of conventional looks.